Should I Stay or Should I Go? Perceived Barriers to Pursuing a University Education for Persons in Rural Areas - Friesen, Laura; Purc-Stephenson, Rebecca J. (Canadian Journal of Higher Education, 2016)
A university education can provide an individual with greater employment options, higher income potential, and improved health and quality of life, yet young persons from rural areas remain less likely to attend university than their urban counterparts. This study explores the perceived personal, social, and cultural factors that might create barriers for young persons from rural areas. Semi-structured interviews were conducted with 17 individuals living in rural areas in Alberta, aged 18 to 23 years, who had not attended university. Using interpretative phenomenological analysis, we identified 11 major themes, which were then organized into a conceptual model to illustrate the interacting nature of these factors and their influence on a person’s decision to pursue a university education. An examination of this model and its associated themes may help reveal the possible barriers young persons from rural areas experience when deciding whether or not to attend university.